Where is Science Going? An Interview with Professor Giorgio Agamben - Pensotti, Andrea (Organisms. Journal of Biological Sciences, 2021)
The current use of science as an argument for political purposes reveals an old bias: the idea that science is about truth and therefore is potentially authoritarian. In reality, science is about doubt. The public management of the COVID pandemic should make us reflect about several aspects of our society.